2013
DOI: 10.2218/ijdc.v8i2.263
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary differences in faculty research data management practices and perspectives

Abstract: Academic librarians are increasingly engaging in data curation by providing infrastructure (e.g., institutional repositories) and offering services (e.g., data management plan consultations) to support the management of research data on their campuses. Efforts to develop these resources may benefit from a greater understanding of disciplinary differences in research data management needs. After conducting a survey of data management practices and perspectives at our research university, we categorized faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
137
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 23 publications
18
137
2
Order By: Relevance
“…Many interviewees expressed concern over lack of time and resources for preparing data for sharing, a pattern seen elsewhere in the literature (e.g. McLure et al 2014, Doty 2012, Akers & Doty 2013. Cragin et al (2010) also found that researcher attitudes towards research data sharing were colored by the amount of time it would take to prepare data for sharing.…”
Section: Interview Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Many interviewees expressed concern over lack of time and resources for preparing data for sharing, a pattern seen elsewhere in the literature (e.g. McLure et al 2014, Doty 2012, Akers & Doty 2013. Cragin et al (2010) also found that researcher attitudes towards research data sharing were colored by the amount of time it would take to prepare data for sharing.…”
Section: Interview Resultsmentioning
confidence: 82%
“…Almost without exception, survey and interview research exploring data management and sharing practices in academia exhibit striking homogeneity including: a general lack of data sharing through repositories and journals in favor of sharing via personal communication, researchers rarely creating metadata or other documentation for data, backup and storage practices that are of questionable efficacy and on questionable media, and concerns among researchers about the amount of time required to prepare data for sharing and the potential for misuse of data (Akers & Doty, 2013;Doty, 2012;Editorial, 2011;Parham, Bodnar, & Fuchs 2012;Steinhart, Chen, Arguillas, Dietrich, & Kramer, 2012;Cragin, Palmer, Carlson, & Witt, 2010;Peters & Dryden, 2011). On the other hand, the literature is similarly replete with survey and interview results suggesting that researchers are interested in training and guidance for research data management best practices (Akers & Doty, 2013;Parham et al, 2012;McClure, Level, Cranston, Oehlerts, & Culbertson, 2014, Wright et al, 2013.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a common set of questions enabled us to compare the data formats used by faculty at VCU to those used by faculty at Northwestern (Buys & Shaw, 2015, Figures 1 and 2). Similarly, we reused the reasons for not sharing data from a survey at the NIH Library by Federer, Lu, and Joubert (2015); the questions pertaining to storage amounts, data storage, and backup meth-ods came from Akers and Doty (2013) at Emory University. By making surveys comparable to others, it becomes possible to perform a meta-analysis of institutional surveys to provide deeper insight into the data behaviors of researchers.…”
Section: Case Study: Virginia Commonwealth Universitymentioning
confidence: 99%
“…However, inconsistencies extend further than a definition of terms. Previous studies evidence wide variation in practices surrounding research data: differences in how data are collected, stored, and shared (Bishoff & Johnston, 2015;Kennan & Markauskaite, 2015;Tenopir et al, 2011Tenopir et al, , 2015; among disciplines, institutions, departments, and individuals (Akers & Doty, 2013;Buys & Shaw, 2015;Weller & Monroe-Gulick, 2014); and in researchers' experience, knowledge, and perceptions (Akers & Doty, 2012;Jahnke & Asher, 2012;Scaramozzino, Ramírez, & McGaughey, 2012). When viewed collectively, it is evident that librarians must recognize and address those needs that are relevant to their specific users.…”
Section: Introductionmentioning
confidence: 99%